Los recursos didácticos concretos en el rendimiento académico en el área de Matemática a los niños del Segundo año de Educación Básica paralelo “B” de la Unidad Educativa José María Román provincia de Chimborazo, cantón Riobamba, año lectivo 2015-2016. - Allauca Guevara, María Fernanda (2016)
The research was carried out in Unidad Educativa José María Román, its purpose is to determine that the specific didactic resources contribute in the academic performance of mathematics area to the children of Second year class “B”. In addition, it intends to establish the importance of using materials in the students' learning. The used methodology was deductive and inductive. The research design is non-experimental. The level of research is diagnostic and explanatory. The types of research are field and documentary because it investigated the reality of the facts with the participants, having as a population 25 boys and 14 girls from Second year class "B". The applied technique was an observation sheet and a survey which were addressed to teachers. The analysis and interpretation of results was done in tables, percentages and graphs that allowed to observe the results in a better way. As a conclusion of this research, it established that the use of didactic material favors the mathematics learning which are considered as didactic tools that allows students to assimilate knowledge easily and it develops skills, logical thinking, creativity and imagination.